PROBLEMATIKA SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) DARI DIMENSI : SUBJEK, OBJEK DAN KEPENTINGAN YURIDIS - Sayuna, Inche (REPERTORIUM, 2014)
Abstractpower of Attorney charge Mortgage (SKMHT) is the power of a special nature , do not contain legal power to do anything other than charge Mortgage . SKMHT must be made by deed of Notary / ppAT deed . SKMHT arrangements stipulated in law No. 4 of 1996 regarding Mortgage , Jo pERKABAN No. 8 of 2012 jo pERMENAG No. 4 of 1996 About Determination Deadlines power of Attorney Impose Usage Rights Mortgage. Implementation of these rules to meet a number of problems both dimensions Subject , Object and Juridical Interests . The problems concerning the subject of discussion on the prohibition of the power of substitution to the principle of publicity of a power of attorney that can be subsituted. The problems concerning the Object , questioned about the time period stipulated in PERMENAG SKMHT 4 , of 1996 , and Problems juridical interests associated with Notary authority in making SKMHT which requires a notary to make a deed based format standard form set out in pERKABAN No. 8 of 2012 which is considered contrary to law No. 2 of 2014 , especially with regard to the provision of an authentic deed.AbstrakSurat Kuasa Membebankan Hak Tanggungan (SKMHT) merupakan kuasa yang bersifat khusus, tidakmemuat kuasa untuk melakukan perbuatan hukum lain selain membebankan Hak Tanggungan. SKMHT wajibdibuat dengan akta Notaris/Akta PPAT. Pengaturan SKMHT diatur dalam UU No. 4 Tahun 1996 tentangHak Tanggungan junto Peraturan Menteri Negeri Agraria (PERMENAG) No.8 Tahun 2012 junto PeraturanKepala BPN RI (PERKABAN) No. 4 Tahun 1996 tentang Penetapan Batas Waktu Penggunaan Surat KuasaMembedakan Hak Tanggungan. Implementasi dari aturan aturan tersebut menemui sejumlah persoalan baikdari dimensi Subjek, Objek dan Kepentingan yuridis. Problematika Subjek menyangkut tentang larangankuasa substitusi dengan asas publisitas dari surat kuasa yang bisa disubstitusikan. Problematika tentang Objek,mempersoalkan tentang jangka waktu SKMHT sebagaimana diatur dalam PERMENAG 4 Tahun 1996, danProblematika Kepentingan yuridis berkaitan dengan kewenangan Notaris dalam pembuatan SKMHT yangmewajibkan notaris untuk membuat akta berdasarkan format blanko standart yang diatur dalam PERKABANNo. 8 Tahun 2012 yang dianggap bertentangan dengan UU No. 2 Tahun 2014, khususnya yang berkaitandengan ketentuan tentang bentuk akta otentik.